THE PROSTITUTE AS A CITY’S PARADOX: NAVIGATING THE SOCIETY THROUGH THE BODY OF THE FALLEN WOMEN IN THE SELECT STORIES OF SAADAT HASSAN MANTO (Proceedings of the World Conference on Women’s Studies, 2022)
Saadat Hassan Manto’s scathing treatment of the society and the people that live in it makes him create a distinct space for himself in the socio-literary environment of Indian literature. Materializing his enterprise, Manto’s female characters stand out and speak for the sadomasochist society. The Prostitution industry -through the eyes of Manto displays the dark underbelly of the developing city thus manifesting into commodified human existence. This paper would discuss stories like, ‘Boo’, ‘Haatak’, ‘Kaali Salwar’and ‘Dus Rupaiyaa’ to talk about the ever-growing malaise of sex-slavery and the society amongst which such animosity harbors.  The poverty and destitution in Manto’s world draw a parallel to contemporary India thus making it all the more important for internalizing him and his iconoclastic ideas. The tattered society that existed then just like it does now symbolize the fact that prostitutes are a transacted handiwork of a diseased social order. The women who are a part of it and the others who compliment the functioning of this infested vicious cycle are reduced to live on the remains of the society. The stories remind us that they are not regionalist case of sexual slavery but they point out to the incessant sexual oppression that Indian women face everywhere. This paper would extensively use the above-mentioned works of the author to paint a picture of the degenerate world around what surprisingly appears to be symptomatic of contemporary India.
Keywords: sexual oppression; underbelly; animosity